Freeport-McMoRan : financing an acquisition - Stowell, David P.; Rossmann, Peter (London : SAGE Publications Ltd, 2017)
Freeport-McMoRans acquisition of Phelps Dodge created the worlds largest publicly traded copper company. JPMorgan and Merrill Lynch advised the acquirer and arranged $17.5 billion in debt financing and $1.5 billion in credit facilities. In addition, these two firms underwrote $5 billion in equity capital through simultaneous offerings of Freeport-McMoRan common shares and mandatory convertible preferred shares. These financings created an optimal capital structure for the company that resulted in stronger credit ratings. The activities of the equity capital markets and sales groups at the underwriting firms are explored and the structure and benefits of mandatory convertible preferred shares is explained.
Originally published: Stoweel, D. P., & Rossmann, P. (2007). Freeport-McMoRan: Financing an acquisition. 5-407-751. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Freeport-McMoRan Copper & Gold Inc. -- Case studies; Mineral industries -- Indonesia -- Case studies; Gold mines and mining -- Indonesia -- Case studies